"Because for us, as Europeans, it is only normal again when we are great again": metapolitical whiteness and the normalization of white supremacist discourse in the wake of Trump. Issue 13 (21st October 2021) - Paul, Joshua
ABSTRACT: The purported utopian multiculture of the Obama era has shown itself to be little more than a postracial fantasy with structural racism persisting and indeed intensifying. The short-lived illusion of harmony and "progress" experienced a significant rupture with the "white backlash" in 2010 and evolved into a pervasive social force with Trump's election. This article analyses the resurgence of a mainstreaming white nationalism following the 2016 presidential election using data drawn from websites, interviews with and publications by the alt-right. Through the concept of metapolitical whiteness, it argues that a new conjuncture of white racial politics has emerged since 2016. This is predicated on the normalization of white supremacist discourse which utilizes novel forms of disseminating its message to a younger demographic. Ultimately, it contends that white supremacist discourse is re-entering mainstream political discourse and popular culture through ironic comedy and differentialist discursive strategies borrowed from the French new right.